Integrasi Perkembangan Kognitif Individu dalam Al-Qur’an dengan Aspek Religius - Iman Asroa BS; Wahidah Fitriani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The study of individual cognitive development is something that has been studied quite often by many researchers. The study is in the form of individual cognitive development related to the process of education and learning, student age development, character formation, ability to read and understand the Qur'an, and Islamic perspective on individual cognitive development. The purpose of this study was to find the integration between individual cognitive development and individual religious aspects as learners. The research question is how is the integration of individual cognitive development in the Qur'an with religious aspects? The research was conducted qualitatively with the literature study method. Data collection was carried out by examining verses of the Qur'an, books of commentary and various scientific articles related to cognitive development, religious aspects and the integration of the two. The data findings were analyzed using the Miles & Hubberman technique and presented descriptively in the form of a narrative. The results of the study found that there was an integration of individual cognitive development with religious aspects. This is indicated by the content and interpretation of the verses of the Qur'an regarding the use of the human mind to understand the power of Allah. related to cognitive integrated with religious values.